Genetic analysis of post‐pandemic 2010–2011 influenza A(H1N1)pdm09 hemagglutinin virus variants that caused mild, severe, and fatal infections in Northern Greece. Issue 1 (5th June 2014) - Melidou, Angeliki; Gioula, Georgia; Exindari, Maria; Chatzidimitriou, Dimitris; Malisiovas, Nikolaos
<x xml:space="preserve">Abstract</x> Since its appearance, influenza A(H1N1)pdm09 caused considerable morbidity and mortality in Northern Greece. Genetic analysis of post‐pandemic circulating strains scoped to investigate any correlation between genetic variations that emerged during viral evolution and severity of infection. Pharyngeal swabs/aspirates (n = 1, 870) were examined with real‐time reverse transcription‐polymerase chain reaction. Hemagglutinin sequences were analyzed on 110 strains (37 fatal/73 non‐fatal cases), followed by statistical and phylogenetic analysis. Influenza A(H1N1)pdm09 was detected in 848 samples. Coexistence of clusters 3, 4, 5, 6, and 7 indicated co‐circulation of lineages in Northern Greece. Genetic analysis showed that HA sequences had 96–99% sequence similarity with the vaccine strain and that there was no association between any co‐circulating lineage and severity. Several viruses accumulated variations in HA antigenic sites. D222G was significantly associated with fatal infections, supporting its association with increased viral pathogenesis. On the other hand, four variations were associated with milder disease outcomes. Certain signature amino acid changes persisted during and/or after the pandemic, indicating their offer of selective advantages to the virus. Negative selection was observed in 70% of pandemic variations as they probably did not contribute to the virus fitness. It is of interest that persistent variations were highly identified in the vicinity of antigenic or receptor‐binding sites. Of those, K171R was associated only with fatal infections. Also of interest, only strains that were isolated from fatal infections had variations that altered both their acid–base and polarity properties. Genetic changes that may alter the antigenicity, pathogenicity and transmissibility of circulating virus variants need to be determined and closely monitored. J. Med. Virol. 87: 57–67, 2015. © 2014 Wiley Periodicals, Inc.